Ovulation Induction and Controlled Ovarian Stimulation A Practical Guide - Homburg, Roy.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The second edition of this highly successful book updates the reader on progress and developments in the field of ovulation induction and controlled ovarian stimulation. Furthermore, it provides the busy clinician with a reliable overview of the principles involved and the management needed. As with the previous edition, the emphasis throughout this book is on logical evidence and evidence-based solutions, supplemented with Professor Roy Homburg’s extensive clinical experience gleaned from more than forty years working in the field. A number of highly useful algorithms and explanatory tables reinforce this approach, ensuring that the reader is presented with easy-to-grasp, well-presented information that maximizes clarity and understanding. Ovulation Induction and Controlled Ovarian Stimulation: A Practical Guide offers a concise, no-nonsense, practical guide to ovulation induction and controlled ovarian stimulation and will be an essential resource for general gynaecologists, fertility specialists and trainees, health workers and students.
Introduction -- A potted history of ovulation induction -- Physiology of ovulation -- Diagnosis and causes of anovulation -- General factors influencing ovarian function and the prognosis for ovulation induction -- Assessment of ovarian reserve -- Management of hypogonadotrophic-hypogonadism -- Understanding the problems of treating PCOS -- Anti-oestrogens -- Low-dose gonadotrophin therapy for ovulation induction -- Insulin lowering agents -- Laparoscopic ovarian drilling -- Management of hyperprolactinaemia -- Gonadotrophins for ovulation induction -- Unexplained infertility -- Controlled ovarian stimulation for intra-uterine insemination -- Controlled ovarian stimulation for IVF/ICSI -- Management of poor responders -- Management of high responders -- Mild stimulation protocols -- Ovarian hyperstimulation syndrome -- Multiple pregnancies -- Future perspectives.
Keywords: Reproductive medicine; Gynecology .; Maternal and child health services; Endocrinology .; Reproductive Medicine; Gynecology; Maternal and Child Health; Endocrinology